Wirelessly Pattern Reconfigurable Yagi Antenna Based on Radio Frequency Identification - Chuankui Shen; Zhengxing Wang; Liekun Yang; Fengcheng Mei; Terry Tao Ye (International Journal of Antennas and Propagation)
This paper presents, for the first time, the implementation of a pattern reconfigurable Yagi-Uda antenna utilizing radio frequency identification (RFID) technology for remote pattern control. The proposed scheme emphasizes the use of wireless communication instead of long metal cables, resulting in improved stability of the antenna’s pattern and return loss. Two low-power consumption single-pole-double-throw (SPDT) switches are employed on a passive resonator, enabling it to function as a director or reflector under the long-range control (up to 25 m) of an RFID reader. Measurement results demonstrate a −10 dB impedance bandwidth of 4.2% and a gain of 7 dBi at 2.41 GHz. The entire system operates with an ultra-low power consumption of 12 μW.